Mapping the Frontier of Fraud and Artificial Intelligence: An Analysis of Scholarly Publications - Kamilah, Raida Shafa; Koeswoyo, Poppy Sofia; Irawady, Cahya (Universitas Muhammadiyah Pontianak, 2026)
The advancement of digital technology has transformed financial fraud prevention. While AI enables real-time, accurate fraud detection, it also poses risks through misuse, such as deepfakes and identity theft. This study maps global research on AI in fraud detection using bibliometric analysis of 146 Scopus-indexed articles. Results highlight a surge in publications since 2020, led by India, the UK, and South Africa. Core themes include fraud detection, risk assessment, and decision making, with emerging topics like AI explainability and chatbots. This study offers a comprehensive overview to guide future research and strengthen adaptive fraud prevention strategies.